Exploring the salt–cocrystal continuum with solidstate NMR using natural-abundance samples: implications for crystal engineering. (2017) - Rajput, Lalit; Banik, Manas; Yarava, Jayasubba Reddy; Joseph, Sumy; Pandey, Manoj Kumar; Nishiyama, Yusuke; Desiraju, Gautam R.
No abstract available